PREPARATION OF INFORMATION ON THE EXTERNAL CONTOURS OF FLAT GEOMETRIC OBJECTS FOR EFFECTIVE AUTOMATED DESIGN OF RATIONAL CUTTING SCHEMES - ЧУПРИНКА, В. І.; ЧУПРИНКА, Н. В.; ВАСИЛЕНКО, О. Л.; НАУМЕНКО, Б. В. (Technologies and Engineering, 2023)
Purpose. To develop mathematical and software for preparing information about the external contours of flat geometric objects for effective automated design of rational schemes for cutting materials for these flat geometric objects. Methodology. During the development of algorithms for the preparation of information about the external contours of flat geometric objects with acceptable approximation accuracy, the methods of analytical geometry and applied mathematics were used. Findings. For the effective use of the software for the automated design of rational schemes for cutting materials into flat geometric objects, algorithms for preparing information about the external contours of flat geometric objects with acceptable accuracy are proposed, which ensure a reduction in the time of automated design of rational schemes for cutting several times. This is especially important for interactive design and correction of cutting patterns. After analyzing the value of the exact display coefficient for a given approximation accuracy, it is recommended to select the allowable approximation accuracy for automatic preparation of information about the external contours of shoe parts in the range of 0.5 mm ≤ ε ≤ 0.25. Originality. Algorithms for preparing information about the external contours of flat geometric objects for efficient automated design of rational schemes for cutting materials for these flat geometric objects are proposed, which determine the permissible accuracy of the piecewise linear approximation of these contours and ensure their approximation with this permissible accuracy. Practical value. The proposed algorithms for preparing information about the external contours of flat geometric objects for efficient automated design of rational schemes for cutting materials for these flat geometric objects were implemented in a software product for compacting information about external contours during piecewise linear approximation of these contours. As a result of compaction, the information obtained about the external contours of flat geometric objects will reduce the time of automated design of rational cutting patterns by several times.